Cohort profile: The WHO Child Mortality Risk Stratification Multi-Country Pooled Cohort (WHO-CMRS) to identify predictors of mortality through early childhood - Schwinger, Catherine; Kaldenbach, Siri; Berkley, James A; Walson, Judd L; Argaw, Alemayehu; Chowdhury, Ranadip; Strand, Tor A.; Rollins, Nigel; WHO Risk Stratification Working Group; Becquey, Elodie; Huybregts, Lieven; Leroy, Jef L.; et al. (BMJ, 2024)
Purpose To provide details of a pooled data set that will be used to estimate absolute and relative mortality risks and other outcomes among children less than 59 months of age and the predictive performance of common risk exposures, both individually and in combination.